2019
DOI: 10.1016/j.taap.2019.02.013
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of CpG-ODN-mediated IFNα and TNFα response in human plasmacytoid dendritic cells (pDC) by cannabinoid receptor 2 (CB2)-specific agonists

Abstract: Plasmacytoid dendritic cells (pDC) compose 0.2-0.5% of circulating leukocytes but play a significant role in mounting host immune responses. Elevated and chronic activation of pDC are implicated in autoimmune disease like systemic lupus erythematosus and rheumatoid arthritis. Δ 9tetrahydrocannabinol (THC) is a well characterized cannabinoid with potent anti-inflammatory activity, but acceptance of THC as a treatment for autoimmune disorders has been hindered due to psychotropic activity. The psychotropic effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 60 publications
(68 reference statements)
0
15
0
Order By: Relevance
“…There are two recent studies focused on CpG stimulation of IFN-a production from human plasmacytoid dendritic cells. 133,134 While these studies are focused primarily on THC and other CB 2 agonists, CBD was also used (1-10 lM) and did not affect IFN-a production. 133,134 It was interesting, however, that CBD suppressed the CD83 dendritic cell activation marker on dendritic cells derived from HIV + , but not healthy, individuals.…”
Section: Cbd Effects and Mechanisms Of Immune Suppression In Innate Cmentioning
confidence: 99%
See 1 more Smart Citation
“…There are two recent studies focused on CpG stimulation of IFN-a production from human plasmacytoid dendritic cells. 133,134 While these studies are focused primarily on THC and other CB 2 agonists, CBD was also used (1-10 lM) and did not affect IFN-a production. 133,134 It was interesting, however, that CBD suppressed the CD83 dendritic cell activation marker on dendritic cells derived from HIV + , but not healthy, individuals.…”
Section: Cbd Effects and Mechanisms Of Immune Suppression In Innate Cmentioning
confidence: 99%
“…133,134 While these studies are focused primarily on THC and other CB 2 agonists, CBD was also used (1-10 lM) and did not affect IFN-a production. 133,134 It was interesting, however, that CBD suppressed the CD83 dendritic cell activation marker on dendritic cells derived from HIV + , but not healthy, individuals. 134 Reduction in dendritic cell CD83 signaling can compromise T cell function, 135 although additional studies using CBD in human dendritic cells and T cells are needed to establish the consequences of CBDinduced reduction in CD83 on HIV + dendritic cells.…”
Section: Cbd Effects and Mechanisms Of Immune Suppression In Innate Cmentioning
confidence: 99%
“…Using molecular docking and molecular dynamics analyses, Fechtner et al showed that JWH-015 favourably bound to glucocorticoid receptor (GR), and GR knockdown reduced the anti-inflammatory effect of JWH-015 [ 129 ]. JWH-015 and JWH-133 modulate interferon α (IFNα) and TNFα responses in primary human plasmacytoid dendritic cells [ 130 ]. In an in vitro study of IL-1β-stimulated synoviocytes, JWH-133 mediated the association of CB 2 with TAK1 kinase to increase nuclear translocation of the transcription factors NF-κB p65 and AP-1 [ 110 ].…”
Section: Introductionmentioning
confidence: 99%
“…In human monocytederived dendritic cells (DCs), the expression of all the components of the ECS has been described [64] and several inflammatory models showed the capacity of cannabinoids to modulate DC function. AEA and THC inhibit pro-inflammatory cytokine production and the capacity of DCs to polarize Th1 and Th17 responses [65][66][67]. THC induces apoptosis in murine DCs, providing a potential immunosuppression mechanism of immune cells [68].…”
Section: Regulation Of Immune Cells By Cannabinoidsmentioning
confidence: 99%
“…Metabolic reprogramming can govern the function of T cells, macrophages, and DCs. Immune activation is mainly linked to a glycolysis-driven upregulation of anabolic processes, [184,185] AEA, 2-AG, THC, and CBD inhibit cytokine production [61,81,186,187] AEA and PEA stimulate phagocytosis [188,189] 2-AG, THC, and WIN55212-2 modulate ROS production [187,190] CBD induces apoptosis [191] Dendritic cells (DCs) CB1 and CB2 [43,64] AEA, THC, JWH-015, and JWH-133 inhibit inflammatory cytokine production [65,66] AEA and THC inhibit the capacity to induce Th1 and Th17 responses [65,67] THC induces apoptosis [68] THC impairs human monocyte-derived DC differentiation [192] Neutrophils CB1 and CB2 [70,193] AEA, CBD, and CB2 signalling reduce cell migration [69,70] AEA and 2-AG induce cell activation and the release of antimicrobial effectors [70,71,194] NK cells CB1 and CB2 [60] 2-AG and THC inhibit cytolytic activity [72,74] CB2 signalling reduces cell migration [74] O-1602 induces high cytolytic activity and cytokine production [49] Eosinophils CB1 and CB2 [195] 2-AG increases cell recruitment [195,196] WIN55212-2 reduces cell recruitment [197] Mast cells CB1 and CB2 [73,103,198] AEA and AEA-derived compounds inhibit cell maturation and degranulation…”
Section: Anti-inflammatory Mechanisms Of Cannabinoidsmentioning
confidence: 99%